Structure of a glycoglucuronomannan from the low-viscosity gum of Vochysia lehmannii - Wagner, R.; Woranovicz-Barreira, S. M.; Iacomini, M.; Delgobo, C. L.; Pimentel, N. M.; Gorin, PAJ (Elsevier B.V., 2004)
The polysaccharide (VSP) from the gum exudate of quaruba (Vochysia lehmannii) had two components of almost identical M. centred at 24,800, as shown by HSPEC-MALLS. The presence of aggregates was shown since carboxy-reduction gave VSP-RED, which contained low molecular weight components with M-w 19,000 > 5800 and polydispersity ratios dn/dc 0.160 and 0.149, respectively. VSP formed low viscosity aqueous solutions and acid hydrolysis gave Man (30%), Ara (16%), Gal (10%), and Glc (14%). The latter arose partly from GlcA (30%). Methylation analysis revealed mainly neutral units of 2-O- (60%) and 2,3-di-O-substituted Manp (5%), and those of nomeducing ends (8%), 2-O- (3%), and 4-O-substituted Arap and/or 5-O-substituted Araf units (6%). VSP-RED contained Glc (45%), Man (35%), and Ara (13%) and methylation analysis indicated mainly 4-O-substituted Glcp (31%) and 2-O- (51%) and 2,3-di-O-substituted Manp units (5%). A predominant alternating structure for VSP was shown by its C-13 NMR spectrum, which contained 10 main signals and a small one of C-6 of GlcpA. This was confirmed by formation, on partial hydrolysis of VSP, of a tetrasaccharide, which was characterised by NMR spectroscopy and ESI-MS as beta-GlcpA-(1 --> 2)-alpha-Manp-(1 --> 4)-beta-GlcpA-(1 --> 2)-Man, which arose from the main chain, thus confirming VSP to be a glycoglucuronomannan. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Vochysia lehmannii; gum polysaccharide; aggregates; low viscosity; glycoglucuronomannan; Araf side chains